2019
DOI: 10.1021/acs.jnatprod.9b00504
|View full text |Cite
|
Sign up to set email alerts
|

An Acetylenic Lipid from the New Zealand Ascidian Pseudodistoma cereum: Exemplification of an Improved Workflow for Determination of Absolute Configuration of Long-Chain 2-Amino-3-alkanols

Abstract: An acetylenic 2-amino-3-alcohol, distaminolyne B (2), isolated from the New Zealand ascidian Pseudodistoma cereum, is reported. The isolation and structure elucidation of 2 and assignment of 2S,3S absolute configuration (AC) using the exciton coupled circular dichroism technique are described. Using a methodologically facile workflow, the same AC was also established by analysis of specific rotation, terminal methyl C-1 δ C chemical shift, and NH δ H and J values of the N,O-diacetate derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The CD spectrum of 4 (MeCN) showed two strong Cotton Effects [λ 226 (Δε −62.4) and λ 243 (Δε −66.5)] consistent with threo -(2 R ,3 R ) configuration . Notably, semisynthetic studies confirmed the absolute configuration proposed by the specific rotation and 13 C NMR shifts comparison model and halaminol E ( 2 ), is a rare naturally occurring (2 R ,3 R ) analogue in the 2-amino-3-alkanol series.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The CD spectrum of 4 (MeCN) showed two strong Cotton Effects [λ 226 (Δε −62.4) and λ 243 (Δε −66.5)] consistent with threo -(2 R ,3 R ) configuration . Notably, semisynthetic studies confirmed the absolute configuration proposed by the specific rotation and 13 C NMR shifts comparison model and halaminol E ( 2 ), is a rare naturally occurring (2 R ,3 R ) analogue in the 2-amino-3-alkanol series.…”
Section: Resultsmentioning
confidence: 55%
“…Recently, it was proposed that the absolute configuration of 2-amino-3-alkanols can be determined upon comparison of the specific rotation and 13 C NMR shifts of their N,O-diacetyl derivatives with the sign of the rotation being indicative of the absolute configuration at C-2 and the chemical shift for the C-1 methyl being indicative of the relative configuration of the threo and erythro diastereomers. 12 The N,O-diacetyl halaminol E exhibited dextrorotatory specific rotation ([α] D +15, c 0. configuration, while the 13 C NMR chemical shift in chloroform-d of the C-1 methyl group (δ C 17.9) was consistent with a threo configuration, suggesting the absolute configuration of 2 to be (2R,3R). However, the review exemplified only one (2R,3R) analogue 13,14 with no 13 C NMR shifts of its C NMR shifts comparison model 12 and halaminol E (2), is a rare naturally occurring (2R,3R) analogue in the 2-amino-3alkanol series.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation